Cornetor Trumpet: Specially Composed for the progressing Brass Student - COOK, H.A. Vander (Rubank Inc., 1938)
Lyra, Vega, Cygnus, Altair, Spica, Antares, Centaurus, Orion, Sirius, Mira, Arcturus, Rigel